2020
DOI: 10.2147/mder.s241205
|View full text |Cite
|
Sign up to set email alerts
|

<p>In Quest of Pathognomonic/Endophenotypic Markers of Attention Deficit Hyperactivity Disorder (ADHD): Potential of EEG-Based Frequency Analysis and ERPs to Better Detect, Prevent and Manage ADHD</p>

Abstract: Attention deficit hyperactivity disorder (ADHD) is a chronic heritable developmental delay psychiatric disorder requiring chronic management, characterized by inattention, hyperactivity, hyperkinectivity and impulsivity. Subjective clinical evaluation still remains crucial in its diagnosis. Discussed are two key aspects in the "characterizing ADHD" and on the quest for objective "pathognomonic/endophenotypic diagnostic markers of ADHD". The first aspect briefly revolves around issues related to identification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 233 publications
(241 reference statements)
0
8
0
Order By: Relevance
“…Since July 6th 1924, when the first EEG was recorded, it has evolved from being an add-on tool in the diagnosis of brain health, to an instrument that is used for diagnosis, diseasestaging, evaluation of prognosis, monitoring the course of treatment (pharmacotherapy and chemotherapy), and as a therapeutic tool [14][15][16][17][18][19][20][21][22][23]. The EEG allows for clinical decision making and non-invasive assessment of the functioning of the 4mm thick cerebral cortex, which governs our mental, neurological, neuromuscular and physiological well-being [14,15].…”
Section: The Eegmentioning
confidence: 99%
“…Since July 6th 1924, when the first EEG was recorded, it has evolved from being an add-on tool in the diagnosis of brain health, to an instrument that is used for diagnosis, diseasestaging, evaluation of prognosis, monitoring the course of treatment (pharmacotherapy and chemotherapy), and as a therapeutic tool [14][15][16][17][18][19][20][21][22][23]. The EEG allows for clinical decision making and non-invasive assessment of the functioning of the 4mm thick cerebral cortex, which governs our mental, neurological, neuromuscular and physiological well-being [14,15].…”
Section: The Eegmentioning
confidence: 99%
“…Moreover, a recent study of nearly 28 000 twins estimated the genetic correlation ( r g ) between clinically-diagnosed ADHD and parent-rated ADHD symptoms at 0.56 and reported that 89% of this association could be attributed to genetic factors (Taylor et al, 2019). Twin and family studies have also elucidated the etiology underlying several cognitive and neurobiological features associated with ADHD (for reviews on current understanding of the neurobiology of ADHD, see Faraone et al, 2021; Miranda, Cox, Alexander, Danev, & Lakey, 2020). ADHD or ADHD traits share genetic factors with various executive functions such as reaction time variability and response inhibition (Crosbie et al, 2013; Kuntsi et al, 2010, 2014; Michelini et al, 2021; Tye, McLoughlin, Kuntsi, & Asherson, 2011) as well as brain-based electroencephalographic (EEG) measures (McLoughlin, Palmer, Rijsdijk, & Makeig, 2014; Michelini et al, 2021; Tye et al, 2011, 2012, 2014).…”
Section: Quantitative Genetic Studies Of Adhdmentioning
confidence: 99%
“…Although studies on the use of EEG to identify biomarkers related to ADHD is promising, at the moment there are several difficulties. One of the main challenges is defining the ADHD population and the different sub-groups [93]. An alternative to EEG-based markers comes from studies from experimental psychology.…”
Section: Searching a Specific Phenotype Across Measurable Traitsmentioning
confidence: 99%